2011
DOI: 10.1007/s10518-011-9252-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the seismic response of existing RC buildings using the extended N2 method

Abstract: Extensive studies have confirmed the good performance of the N2 method, recommended by Eurocode8, when performing pushover analyses in regular structures. However, this procedure shows lack of accuracy in predicting the torsional motion of planasymmetric buildings. In order to overcome this problem, Peter Fajfar and his team have proposed an extension of the method based on a combination of a pushover analysis and of an elastic response spectrum analysis. Since definitive answers about this topic have not yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 14 publications
0
24
0
3
Order By: Relevance
“…As mentioned before, preceding studies showed that plan-wise irregular buildings require 3-D modeling due to the torsional behavior under seismic excitation [13][14][15][16][17][18][19][20][21][22][23][24][25]. Structural schemes of Figure 3 provide evidence that one of the RC structures is irregular in plan.…”
Section: Applied Inelastic Static Proceduresmentioning
confidence: 85%
See 1 more Smart Citation
“…As mentioned before, preceding studies showed that plan-wise irregular buildings require 3-D modeling due to the torsional behavior under seismic excitation [13][14][15][16][17][18][19][20][21][22][23][24][25]. Structural schemes of Figure 3 provide evidence that one of the RC structures is irregular in plan.…”
Section: Applied Inelastic Static Proceduresmentioning
confidence: 85%
“…In the case where irregularities are dominant, those procedures are flawed, since they do not have a robust background. To overcome those deficiencies scientists developed 3D pushover techniques to take into account the torsional effects [13][14][15][16][17][18][19][20][21][22][23][24][25]. In their study Fajfar et al [16] stated that with an increase of plastic deformations the torsional effects tend to decrease.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the N2 method was extended to bridges [11] and base-isolated structures [24][25][26]. In addition, the extended N2 method for asymmetric buildings was rigorously tested on a set of existing real-life buildings [10,27]. Key results obtained in these studies are summarized in later sections of this paper.…”
Section: Development Of N2 Methodsmentioning
confidence: 99%
“…The N2 method has been used to this day for almost every type of building (eg. [5,[9][10][11][12]). However, some limitations still exist, as will be shown later on in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Antoniou and Pinho 2004;Chopra and Goel 2002;Elnashai 2001;Kunnath 2006, 2007;Moghadam and Tso 2002;Poursha et al 2009;Sucuoglu and Günay 2010), in plan (e.g. Bento and Pinho 2008;Bento et al 2010;Bhatt and Bento 2011;Erduran 2008;Lin and Tsai 2008), and in both plan and elevation (e.g. Aydınoglu 2003Aydınoglu , 2004Fujii 2011;Chopra 2010, 2011).…”
mentioning
confidence: 99%